(2) ⇔(y−1)2=(x2+y2)(1−x2−y2)⇒x2+y2≤1⇒|x|≤1mà (x^{2}+y^{2})(1-x^{2}-y^{2}) \leq \frac{1}{4}\Rightarrow (y-1)^{2}\leq \frac{1}{4}\Leftrightarrow \frac{1}{2}\leq y\leq \frac{3}{2} \Rightarrow y>0, |x|\leq 1(\sqrt{x^{2}+1}+1) (x^{2}-y^{3}+3y-2)=(\sqrt{x^{2}+1}+1)(x^{2}-(y-1)^{2}(y+2))\leq (\sqrt{x^{2}+1}+1)x^{2} \leq (\sqrt{2}+1)x^{2}\leq 4x^{2}\Rightarrow x=0;y=1$
(2)
⇔(y−1)2=(x2+y2)(1−x2−y2)⇒x2+y2≤1⇒|x|≤1mà
$(x^{2}+y^{2})(1-x^{2}-y^{2})\leq \frac{1}{4}
\Rightarrow (y-1)^{2}\leq \frac{1}{4}
\Leftrightarrow \frac{1}{2}\leq y\leq \frac{3}{2} \Rightarrow y>0, |x|\leq 1
(\sqrt{x^{2}+1}+1) (x^{2}-y^{3}+3y-2)=(\sqrt{x^{2}+1}+1)(x^{2}-(y-1)^{2}(y+2))
\leq (\sqrt{x^{2}+1}+1)x^{2} \leq (\sqrt{2}+1)x^{2}\leq 4x^{2}
\Rightarrow x=0;y=1$